Mitochondrial dysfunction and diabetes in South Africa: A review - Brendon Pearce; Keenau Pearce (Endocrine and Metabolic Science, 2024)
Type 2 diabetes mellitus (T2DM) is a growing public health concern globally, and more so in developing countries like South Africa where it is characterized by an alarmingly high prevalence. Emerging evidence suggests that mitochondrial dysfunction plays a significant role in the pathophysiology of the disease in this region. This review explores the intricate relationship between mitochondrial dysfunction and T2DM in the context of South Africa by providing an in-depth analysis of the specific mitochondrial factors influencing T2DM. Furthermore, it explores South Africa's unique demographic and epidemiological landscape characterizing its increased susceptibility to T2DM. Understanding the interplay between mitochondrial dysfunction and T2DM is of paramount importance in developing tailored prevention and treatment strategies. A need for further research to elucidate the intricate mechanisms behind this relationship, ultimately aiming to mitigate the diabetes burden in South Africa and beyond is highlighted.